2020
DOI: 10.1016/j.jspr.2020.101658
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of five hermetic bag brands during on-farm smallholder cowpea (Vigna unguiculata L.Walp) storage

Abstract: Cowpea (Vigna unguiculata L. Walp) grain is an important source of protein for smallholder farmers in developing countries. However, cowpea grains are highly susceptible to bruchid attack, resulting in high quantitative and qualitative postharvest losses (PHLs). We evaluated the performance of five different hermetic bag brands for cowpea grain storage in two contrasting agro-ecological zones of Zimbabwe (Guruve and Mbire districts) for an 8-month storage period during the 2017/18 and 2018/19 storage seasons. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Our results revealed that ash contents ranged from 3.2% (Vigna unguiculata) to 4.1% (Phaseolus vulgaris), indicating that they are good sources of minerals (e.g., [47,48]). Moreover, all the studied species revealed an average moisture content ranging from 10.7 ± 0.2 g/100 g in Phaseolus vulgaris to 12.4 ± 0.9 g/100 g in Phaseolus lunatus and we concluded that it is possible to store all these beans with quality, in agreement with other studies (e.g., [49]). Amarteifio et al [50] recorded fibre contents of Cajanus cajan cultivated in Botswana ranging from 9.8 to 13.0 g/100 g, higher than those we obtained (6.3 g/100 g).…”
Section: Chemical Compositionsupporting
confidence: 91%
“…Our results revealed that ash contents ranged from 3.2% (Vigna unguiculata) to 4.1% (Phaseolus vulgaris), indicating that they are good sources of minerals (e.g., [47,48]). Moreover, all the studied species revealed an average moisture content ranging from 10.7 ± 0.2 g/100 g in Phaseolus vulgaris to 12.4 ± 0.9 g/100 g in Phaseolus lunatus and we concluded that it is possible to store all these beans with quality, in agreement with other studies (e.g., [49]). Amarteifio et al [50] recorded fibre contents of Cajanus cajan cultivated in Botswana ranging from 9.8 to 13.0 g/100 g, higher than those we obtained (6.3 g/100 g).…”
Section: Chemical Compositionsupporting
confidence: 91%
“…Naturally infested grain was used in the experiment, and Callosobruchus maculatus was identified as the primary insect pest of stored cowpea grain, which corroborates with previous studies (Ngwenyama, Mvumi, Nyanga, Stathers, & Siziba, 2020; Sanon, Dabiré‐Binso, & Ba, 2011). Polypropylene bags showed the highest rate of insect multiplication achieving at the termination of the experiment 11‐fold of the initial insect population.…”
Section: Discussionsupporting
confidence: 87%
“…Efficacy tests are available for multiple species and commodities from different countries and environmental conditions [ 188 , 193 ]. Recently, Ngwenyama et al [ 194 ] compared the efficacy of five hermetic bag brands (GrainPro Super Grain bags (SGBs) from IVR™; PICS bags; AgroZ ® Ordinary bags; AgroZ ® Plus bags; and ZeroFly ® hermetic bags) with dust with pirimiphos-methyl and found almost identical performance. Due to the high efficacy, low cost, and simple operation of these bags, the potential users are mainly small and medium-sized farms in developing countries.…”
Section: Gas and Vapor Insecticide Application Formulationsmentioning
confidence: 99%
“…Due to the high efficacy, low cost, and simple operation of these bags, the potential users are mainly small and medium-sized farms in developing countries. A drawback of hermetic bags is that the larger grain borer Prostephanus truncatus (Horn) (Bostrichidae) [ 195 ], R. dominica [ 196 ], and rodents [ 194 ] can perforate the plastic liner of some types of bags, which increases the oxygen levels and negatively affects the efficacy of the method. In contrary, Otitodun et al [ 197 ] claimed that the ZeroFly ® bags were not easily penetrated by stored-product insect pests under field conditions.…”
Section: Gas and Vapor Insecticide Application Formulationsmentioning
confidence: 99%